Comparative studies on two formulas of double fortified salt and it’s impact on anemia control - Nair, S; Joshi, K; Chitre, N (Indian Journal of Community Health, 2015)
Introduction: Worldwide 600million preschool children are anemic. Of these more than 50% is due to Iron deficiency anemia (IDA). WHO and CDC (2008) reports state that low income countries have more IDA. During childhood, anemia causes growth retardation, compromised mental abilities, reduced school achievement, impaired motor and cognitive development etc. Iron requirements are always high in developing countries, owing to the fact that, there is always more susceptibility of parasitic infestations and infectious diseases. Loss of appetite and anorexia is a major symptom associated with IDA. It has been postulated that even early stages of Iron deficiency can cause a iron dependent dopamine receptors which alters neuro transmission and in turn cognitive functions. (Liebel et al 1979) Alteration in dopamine is associated with altered perception, memory and motivation (Beard2001). Bhatia and Sheshadri in the year 1993, reported that, iron deficient children perform very less on psychomotor test than non- anemic children. Cognitive tasks involve hippocampal and pre-frontal complex of the brain. An iron deficiency can cause significantly low cognitive impact and behavioral change (Lozoff 2000). Indian diets contain adequate amounts of iron. Since absorption gets affected by phytates and other inhibiting factors, its bio-availability goes down. Apart from that, the intake of meat products which are rich in heme iron is low. Hence, food fortification could be the practical approach to deliberately increase the content of an essential micro-nutrient, in order to improve the nutritional quality of the food supply and provide a public health benefit with minimal health risk (WHO-2004). Public health approaches towards the control and prevention of any deficienciesis to start a supplementation programme of fortification of foods with a suitable minerals and compounds. Along with Iron deficiency, prevalence of Iodine deficiency poses a great challenge to address the issue in public health scenario.The vulnerable groups are the most affected ones. Even though the supplementation program is in place, compliance is not at its optimal levels. India already has an existing program on USI norms to supply iodized salt to all populations. Therefore, double fortification of salt with iron and iodine as a tool to combat these deficiencies was the best thought approach by various scientists. The efforts towards producing a stable formula containing iron merging with iodine together was pioneered by Dr. Narsinga Rao in early 70s with all final inputs to design the formula and launch it by 1984. As a sequel to National Policy in the country, National Institute of Nutrition (NIN) evolved the concept of double-fortified salt (DFS) with iodine and iron for controlling the deficiencies of both these micro nutrients in a single measure as one intervention to control two micronutrient deficiencies. With lot of technical issues, bioavailabilty related issues it took a whale of time for its public utility level and took almost twenty years for localisation of the product into the market.The details of the product is provided in Table1